Dexmedetomidine for Sedation of Neonates with HIE Undergoing Therapeutic Hypothermia: A Single-Center Experience - O'Mara, Keliana; Weiss, Michael D. (American Journal of Perinatology Reports, 2018)
Hypoxic-ischemic encephalopathy (HIE) is a significant cause of morbidity and mortality in neonates. Therapeutic hypothermia reduces the risk of death or disability. Providing optimal sedation while neonates are undergoing therapeutic hypothermia is likely beneficial but may present therapeutic challenges. There are limited data describing the use of dexmedetomidine for sedation in patients undergoing therapeutic hypothermia. The objective of this study is to evaluate the efficacy and short-term safety of dexmedetomidine infusion for sedation in term neonates undergoing therapeutic hypothermia for HIE.
Keywords: hypoxic-ischemic encephalopathy; sedation; dexmedetomidine; neonate